Perbandingan Algoritma Enkripsi GGHN(8,8) dan RC4 Untuk Video Conference - Satriyo, Satriyo; Sediyono, Eko; Fatchurrohim, Adian (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Encryption is a solutions to secure the information transmitted through the medium of communication that can not be intercepted by unauthorized parties. This study implemented two algorithms i.e. RC4 and GGHN (8.8) in video conference. This study compared the speed  of  both  encryption  and  decryption  of  the  encryption  algorithm,  and  perform  measurements  of  bandwidth .  From  the  results  of measurements of the speed can be concluded that the RC4 algorithm is 1.53 times and 1.34 times faster than GGHN(8,8) for encryption and  decryption  audio  data.  The  encryption  and  decryption  video  data  RC4  are  1.44  times  and  1.09  times  faster  than  GHN(8,8). Bandwidth  usage  for  video  conferencing  without  encryption  and  bandwidth  usage  on  a  video  conference  with  RC4  encryption  and GGHN (8.8) is the same.Keywords: Video Conference; RC4; GGHN(8,8); Real Time Protocol.